2021
DOI: 10.33448/rsd-v10i16.23935
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antimicrobiana do extrato, frações e punicalagina da casca do fruto de Punica granatum frente a isolados clínicos de vacas com mastite

Abstract: O objetivo deste estudo foi avaliar a atividade antimicrobiana do extrato, frações e punicalagina purificada da casca do fruto da romã, das variedades granada e wonderful, frente a Staphylococcus Coagulase Positivo (SCP) e Staphylococcus Coagulase Negativa (SCN), isoladas de vacas com mastite. As cascas dos frutos de romã foram secas em estufa, moídas e o extrato etanólico foi preparado por maceração e percolação. As frações foram obtidas por fracionamento líquido-líquido, e a purificação da punicalagina reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Several phytochemicals in pomegranate such as ellagic acid and punicalagin have presented antimicrobial properties. Specifically, in vitro studies showed that punicalagin was able to counteract coagulase-positive Staphylococcus and Coagulase-negative Staphylococcus isolated from cows with mastitis due to its ability to inactivate extracellular microbial proteins [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several phytochemicals in pomegranate such as ellagic acid and punicalagin have presented antimicrobial properties. Specifically, in vitro studies showed that punicalagin was able to counteract coagulase-positive Staphylococcus and Coagulase-negative Staphylococcus isolated from cows with mastitis due to its ability to inactivate extracellular microbial proteins [ 68 ].…”
Section: Resultsmentioning
confidence: 99%